Lexical stress awareness, perception and production among English language student teachers in Malaysia - Ernie, Adnan; Chiew, Poh Shin; Pillai, Stefanie (2019)
We would expect teacher education programmes to provide their student teachers (STs) with knowledge of English phonetics and phonology based on the pedagogic model. However, features of pronunciation in the local variety of English are often ignored. In this paper, we focus on one area of pronunciation: lexical stress. In particular we gauge the level of awareness of English lexical stress among 104 STs from five Institutes of Teacher Education campuses in Malaysia. We then examine if they are able to perceive lexical stress in the pedagogic model, British English. Finally, we look at how these STs realise lexical stress. Based on a Lexical Stress Awareness Test (LSAT), most of them had an intermediate level of awareness. Although the majority of them had difficulties describing the characteristics of stress, most were able identify stressed syllables in the target words. Their ability to identity stress in the LSAT was replicated in the perception task, where the stressed syllable in most of the test words produced by an educated British English speaker were marked ‘correctly’. This suggests that even if the STs speak a variety of English which lacks lexical stress, they were able to identify stressed syllables. Based on a comparison with their production of lexical stress, we discuss if their ability to identify stress translates into their own production. We discuss these findings in relation to the relationship among awareness, perception and production, taking into account differences in the way lexical stress in realised in Malaysian and British English.